American traditional values expressed in the way American parents bring up their children nowadays - Bui, Thu Hang (2020)
This study aims at exploring how American traditional values reflected in the way American bring up their children nowadays. Hence, the process of conducting this research consist of two mains steps. The first is studying different viewpoints of well-known materials to bring a scientific conclusion about typical American traditional values and American parenting method. The second is finding the relationship between these cultural values and American childrearing way including styles and methods. Particularly, the Americans mentioned in the research are White Americans who always represent the majority number of American population. After researching and analyzing various books and references, the researcher discovered some significant findings, which helps readers understand deeper about American culture and people. There are five American traditional values which are individualism, equality, competition, materialism and change specifically contributed to American identity. Moreover, White American parents mostly adopt the authoritative parenting style with some typical child rearing practices. It is interesting to prove that the cultural values expressed significantly in the way American parents bring up their children, which is the reason why American children grow up and bring these American traditional values. Besides, the research also revealed that although American parenting method has many advantages, it has some disadvantages. The implications for parents who pursue raising children in American way are trying to avoid the drawbacks of the method and applying it appropriately